Reaction pathways in the chlorination of amino acids - How, Zuo Tong (Curtin University, 2016)
Chlorination is one of the most widely used disinfection technique in drinking water treatment. However, during chlorination, the chlorine can also reacted with organic matter in the water to produce potentially harmful and odorous by-products. This Thesis investigated the reaction and formation pathways of these potentially harmful and odorous by products from the reaction between chlorine and amino acids and therefore aid in the prevention of the formation of these by-products.